THE PERFORMANCE OF EXPRESSIVE SPEECH ACTS AS FOUND ON WAYNE ROONEY’S FACEBOOK - Tauchid, Ahmad; Rukmini, Dwi (Universitas Negeri Semarang, 2016)
People tended to show off their feelings in public. It meant that certain expressive acts were used. This study was to classify what types of expressive speech act were performed by Wayne Rooney on his Facebook, to describe how the expressive speech acts were performed by Wayne Rooney on his Facebook, and to describe how the effects of expressive speech acts performed by Wayne Rooney on the hearers. This study was using descriptive qualitative approach. The findings were that there were four types of expressive speech act on Wayne Rooneyâ€™s Facebook. They were congratulating, complimenting, thanking, and boasting. Expressive speech act of boasting was the most dominant one, namely 46%. Furthermore, each type was performed by Wayne Rooney either with direct expressive speech acts, or with the addition of preparatory acts, supportive acts, as well as the combination of both of them to modify the head acts as the main messages. Expressive speech acts of congratulating tended to cause the hearers to respond the same as what the speaker intended, namely congratulating. Meanwhile, expressive speech acts of complimenting, thanking, and boasting were most likely to cause the hearers to produce a large number of compliments as the responses.Â